The renaissance of American Indian higher education : capturing the dream - Ah Nee-Benham, Maenette K. P. (Maenette Kapeʻahiokalani Padeken), 1956-; Stein, Wayne J., 1950- (Mahwah, N.J. : Lawrence Erlbaum, 2003)
The Native American Higher Education Initiative (NAHEI), a W.W. Kellogg Foundation project, has supported the development and growth of centers of excellence at Tribal Colleges and Universities across the United States. These are centers of new thinking about learning and teaching, modeling alternative forms of educational leadership, and constructing new systems of post-secondary learning at Tribal Colleges and Universities. This book translates the knowledge gained through the NAHEI programs into a form that can be adapted by a broad audience, including practitioners in pre-K through post-se.
PART I. Introduction -- Journey of the Native American Higher Education Initiative and tribal colleges and universities / Dr. Maenette K.P. Benham -- Developmental action for implementing an indigenous college: philosophical foundations and pragmatic steps / Dr. Wayne J. Stein -- Limitations and alternatives to developing a tribally controlled college / Dr. James Shanley -- PART II. Mapping the trail: charting the future -- Effect of the Native American Higher Education Initiative on strengthening tribal colleges and universities: focus on governance and finance / Dr. Wayne J. Stein, Dr. James Shanley, Timothy Sanchez -- Tribal colleges and universities building community: education, social, cultural, and economic development / Dr. Jack Barden -- Linking tribal colleges and mainstream institutions: fundamental tensions and lessons learned / Richard Nichols, Dr. Gerald "Carty" Monette -- Building tribal communities: defining the mission and measuring the outcomes of tribal colleges / Paul Boyer -- PART III. Nurturing and advocating spirit and voice -- Native leadership: advocacy for transformation, culture, community, and sovereignty / Dr. Valorie Johnson, Dr. Maenette K.P. Benham, Matthew Jason VanAlstine -- Culture and language matters: defining, implementing, and evaluating / Dr. Maenette K.P. Benham, Dr. Henrietta Mann -- Gift to all children: native teacher preparation / Dr. D. Michael Pavel, Dr. Colleen Larimore, Matthew Jason VanAlstine -- PART IV. Extending the reach of tribal colleges and universities -- Student access, retention, and success: models of inclusion and support / Dr. Anna M. Ortiz, Iris HeavyRunner -- Native faculty: scholarship and development / Dr. John W. Tippeconnic, III, Dr. Smokey McKinney -- Information technology and tribal colleges and universities: moving into the 21st century / Dr. Michael O'Donnell, Michelle Mitchell, Al Anderson, Lori Lambert, David Burland, Kim Barber.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Indians of North America -- Education (Higher) -- United States; Indian universities and colleges -- United States; Universités des Peuples autochtones -- États-Unis.; EDUCATION -- Higher; Indian universities and colleges; Indians of North America -- Education (Higher); United States